Gambaran Quality of Work life Perawat di Rumah Sakit Tipe B - Kaluku, Suratno; Saleh, Ariyanti; Kadar, Kusrini S (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2019)
Background. Quality Of Work Life (QWL) is a process in which employees and stakeholders work to improve the quality of life of employees and organizational performance simultaneously. Nurses are one of the service personnel who have greater and longer interactions with patients. QWL is a degree of fulfillment of human needs in the work environment. If human needs have reached, it can increase productivity. This gives an understanding that QWL is the main problem that gives attention to the organization because it allows to increase the participation of members in the organization.Aim. To determine the QWL level of nurses and predictable factors affecting QWL nurses in hospitals.Method. The study uses a cross-sectional approach. The population came from type B hospitals in Makassar, Indonesia with a sample that was meaningful for more than 1 year and respondents obtained 287 nurses. Data were collected by questionnaire and test which was a linear regression with a significance value of 0.001.Results. The results of QWL nurses are at the moderate level and also in each of the QWL dimensions. The best predictors of QWL nurses working in type B hospitals were marital status (b = -0.199) which was able to have an impact on QNWL of 55%.Conclusion. Dimensions and overall QWL nurses are at a moderate level. QWL is important to identify capacity in meeting the needs of both the community and the workplace.